Factors associated with vitamin D levels in Mongolian patients with multiple sclerosis - Myadagmaa Jaalkhorol; Amarsaikhan Dashtseren; Gantuya Magnaibayar; Badrangui Bat-Orgil; Ikuo Tsunoda; Shiirevnyamba Avirmed; Stefania Iaquinto; Viktor von Wyl (PLoS ONE, 2025)
Background Multiple sclerosis (MS) onset is caused by genetic and environmental factors. Vitamin D has been identified as contributing environmental risk factor, with higher prevalence at latitudes further from the equator. Mongolia, at 45°N, has limited sunlight exposure, increasing the population’s risk for vitamin D deficiency. Objectives To compare vitamin D levels between persons with MS (pwMS) and persons without MS and to identify factors associated with low vitamin D. Methods We investigated associations with vitamin D levels using data from MS cases and controls from Mongolia. We used linear mixed-effects regression with fixed effects (case status, sociodemographics, and predefined variables) and participant-specific random intercepts. Results Of 62 participants (31 pwMS, 31 controls), pwMS had lower summer [median 23.00 ng/ml (interquartile range 11.30–31.50) vs. 25.00 ng/ml (19.25–32.00)] and winter vitamin D levels [21.00 ng/ml (10.60–27.60) vs. 23.50 ng/ml (15.55–28.60)], with a smaller seasonal decline. Vitamin D deficiency was more prevalent in pwMS. None of these findings reached statistical significance. Winter season and being breastfed as a child were associated with significantly lower vitamin D levels. Conclusion Vitamin D deficiency was common among pwMS, which could be influenced by behavioural factors. These findings may inform more targeted recommendations for pwMS to maintain sufficient vitamin D levels.